2021
DOI: 10.1002/ett.4313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relay and side information at one encoder on the coverage regions in Gaussian multiple‐access channel

Abstract: The two-user multiple-access relay channel (MARC) is investigated in the presence of side information (SI) available only at the informed transmitter in the present article. First, for the discrete alphabet and memoryless MARC with common and private messages, partial decode and forward strategy at the relay and fixed locations of the nodes, a general achievable rate region is obtained. The SI effect is seen and can be analyzed. Second, we extend the discrete result to a practical communications model: Gaussia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Remark. The above relation (16) shows explicitly by 𝜃 1 the correlation impact on the transmission probability in (15). In other words, ( 16) is reduced to (15) by 𝜃 1 =0.…”
Section: Our Workmentioning
confidence: 97%
See 2 more Smart Citations
“…Remark. The above relation (16) shows explicitly by 𝜃 1 the correlation impact on the transmission probability in (15). In other words, ( 16) is reduced to (15) by 𝜃 1 =0.…”
Section: Our Workmentioning
confidence: 97%
“…The ASR against the P A based on the variations of dependence parameter 𝜃 with 𝜂 = 0.4 F I G U R E 6 GSOP vs P J , for different values of 𝜂 with 𝜀 = 0.2 and 𝜇 = 0.5 against transmission power for different dependence parameter in Figure 7. The required value of transmission probability can be used to determine 𝜂 and corresponding GSOP, as mentioned in (16). Also, it can be observed that GSOP performance can be improved significantly by allocating more power to the artificial noise at the cost of transmission probability.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In [22], the effect of (perfect and nonperfect) SI on the maximum coverage region of GMARC for a fixed rate of the transmitters and a fixed distance between relay and destination is analyzed, using the innovative Copula theory approach. Additionally, Reference [23] presents closed-form expressions derived by the authors for average secrecy capacity (ASC), secrecy outage probability (SOP), and secrecy coverage region (SCR).…”
Section: Related Workmentioning
confidence: 99%